2021
DOI: 10.1111/1756-2171.12384
|View full text |Cite
|
Sign up to set email alerts
|

Taxation and market power in the legal marijuana industry

Abstract: In 2012 the state of Washington created a legal framework for production and retail sales of marijuana. Ten other U.S. states and Canada have followed. These states hope to generate tax revenue for their state budgets while limiting harms associated with marijuana sales and consumption. We use a unique administrative dataset containing all transactions in the history of the industry in Washington to evaluate the effectiveness of different tax and regulatory policies under consideration by policymakers and stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 54 publications
3
9
0
Order By: Relevance
“…It has been possible to find a coefficient for selecting hemp genetic material that provides maximum human welfare [5][6][7][8]. The K coefficient is related to the dimensions of legality, protection, and promotion of human health based on industrial hemp [9][10][11][12][13][14][15][16][17][18][19][84][85][86] and contributes to improving human wellbeing. This is how the K coefficient is linked to TCBD, CBG, CBN and TTHC .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been possible to find a coefficient for selecting hemp genetic material that provides maximum human welfare [5][6][7][8]. The K coefficient is related to the dimensions of legality, protection, and promotion of human health based on industrial hemp [9][10][11][12][13][14][15][16][17][18][19][84][85][86] and contributes to improving human wellbeing. This is how the K coefficient is linked to TCBD, CBG, CBN and TTHC .…”
Section: Discussionmentioning
confidence: 99%
“…Even less new are the concepts of genetic selection of plants to generate human welfare [9][10][11][12]. For its part, the hemp industry requires compliance with the legal regulations imposed by each country so that this productive activity is carried out with good manufacturing practices [13][14][15][16][17][18][19]. In addition, the human brain has an endocannabinoid system that develops the nervous system and activity in the brain, which is useful for new therapies as it is interrelated with treatment status, disease progression, and severity of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…When cannabis use becomes fully legalised, a for‐profit cannabis industry will have a commercial interest in expanding the number of daily consumers [ 34 ]. The profitability of the enormous cannabis markets will give the industry sufficient resources to resist public health regulations, which seems to be happening with the legal cannabis industry in the US [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such cross‐shopping across state boundaries has been observed in a number of settings; for example, Seiler et al. (2021) have found that an increase in tax on sweetened beverages reduced sales in the focal region, but increased sales in neighboring regions that did not see the same tax hike; increasing taxes on alcohol (Conlon & Rao, 2015, 2020; Miravete et al., 2018, 2020), cigarettes (Harding et al., 2012; Lovenheim, 2008; Merriman, 2010), and cannabis (Hollenbeck & Uetake, 2021; Jacobi & Sovinsky, 2016) have had similar geographic demand spillover effects.…”
Section: Hypothesis Developmentmentioning
confidence: 99%